TRANSPORT TECHNOLOGIES RELATED TO THE RESTORATION OF SHIP CARGO MECHANISMS WITH THE LATEST MODIFIED EPOXIES - Buketov, Andrii; Shulga, Yurii (Science-based technologies, 2024)
The development of transport technologies today requires not only the creation of bases for the optimal technical use of vehicles, their technical operation, but also their maintenance and repair. One of the main tasks of transport technologies is the search for new promising scientific directions and their implementation in practice, as well as ensuring the effective use of the latest technologies and innovative methods for the construction or repair of water transport facilities. In this respect, the use of epoxy-based polymer composites is promising. They are characterised by improved adhesive and cohesive properties compared to other known oligomers, which determines the wide range of their application in water transport. In order to improve the properties of epoxy-based adhesives, additives of different physical nature are introduced into the epoxy matrix at the initial stage of moulding. This paper investigates the effect of the modifier d-ascorbic acid on the thermal properties of epoxies to obtain a material intended for the restoration of ship loading mechanisms. Based on the dynamics of heat resistance as a function of d-ascorbic acid concentration, the optimum content of the additive in the epoxy compound was determined, which is 1,25...1,50 pts.wt.for 100 pts.wt.of epoxy resin. The introduction of a modifier into the epoxy oligomer provides composites with the highest heat resistance values of all the materials studied. The heat resistance values increase from 341 K (for the epoxy matrix) to 352...354 K. The mechanism of increasing the heat resistance of an epoxy matrix in the presence of a modifier is substantiated, which involves the interaction of epoxy resin with an additive and a hardener as a result of chemical reactions. As a result of the reactions of structure formation of the compound based on epoxy oligomer and modifier in the presence of polyethylene polyamine, mainly strong chemical bonds of C-O, NH2, O-NH2, N=O, N-O-H, C=N type are formed, which largely determine the increase of cohesive strength of the newly formed modified epoxy matrices. It should be noted that it is the cohesive strength of the matrix that determines the thermal resistance of the material at elevated temperatures. It was found that the maximum glass transition temperature (333 K) was observed for the modified material containing d-ascorbic acid at 1,5 pts.wt. At this level of additive, the maximum values of both heat resistance and glass transition temperature were observed compared to the original epoxy matrix (327 K). At this modifier concentration, the cross-linking of the compound forms the most cross-linked structural network of an amorphous polymer with the highest number of chemical bonds.